Two familial cases of Hb Tyne confirm instability as cause of low expression - Beverley M. Pullon; Stephen O. Brennan (Thalassemia Reports, 2017)
We report a second occurrence of hemoglobin (Hb) Tyne, [β5 (A2) Pro>Ser] HBB:c.16C>T(p.Pro6Ser), which like the first case was associated with normal hematology. We verified the variant was mildly unstable by showing it was greatly enriched in isopropanol precipitates. This minor instability accounts for the slightly decreased expression of the new β chain. The variant was picked up as an interfering component on HbA1c testing using cation exchange high performance liquid chromatography (HPLC). However, this may be an advantage in detecting electrophoretically silent variants. Furthermore, this report also highlights the importance of uneven or sloping baselines on HPLC, which could reflect the presence of a variant hemoglobin even in the presence of normal electrophoresis and full blood count.